Efficacy and Safety of Transcatheter Ventricular Septal Defect Closure Using Nit-Occlud Le VSD coil in Short-term Observation - Saraswati Dewi; Mahrus Abdur Rahman; I Ketut Alit Utamayasa; Taufiq Hidayat (Faculty of Medicine, University of Jember, 2021)
Nit-Occlud Le VSD coil, an alternative device for closing VSD transcatheter, started to be used in dr. Soetomo Hosptal in 2017, but no research has been done on the results of closure with this device. This study aims to evaluate the efficacy and safety of the Nit-Occlud Le VSD coil. Descriptive observational method was used. The results are as follow: Of the 17 patients who underwent transcatheter closure during January to December 2018, 10 (58, 8%) cases were closed with Nit- Occlud Le VSD coil. The success of implantation is 100%, 8 cases were closed with Nit-Occlud Le VSD coil, 2 plus an amplatzer (ADO 1 and AVSO). Type of VSD: perimembranaous 7 (70%), subaortic 2 (20%) and mid muscularis 1 (10%). Immediate complete closure in 7/10 (70%), while 3 (30%) obtained residual DSV. The closure rate at the first month of follow up becomes 80%. Median length of post-catheterization was 2 days (2 - 3 days). Complications: 1 (10%) mild aortic regurgitation, 1 (10%) hemolysis and 2 (20%) with additional second device (ADO 1 and AVSO): first case: moderate residual VSD and severe aortic regurgitation; second case: severe tricuspid regurgitation and residual VSD that disappeared in first month. The residual VSD altered from 30% to 10%, and closure rate was 80% at the first month of observation. VSD closure with Nit-Occlud Le VSD coil provides good efficacy and safety for patients. Keywords: VSD, Nit-Occlud Le VSD coil.